A comparative analysis between Mannheim peritonitis score and acute physiological and chronic health evaluation II score in predicting prognosis of patients of perforation peritonitis - Mishra, Anand; Singh, Krishna Kant; Jain, Vinod (International Journal of Research in Medical Sciences, 2019)
Background: The early assessment and recognition of peritonitis patient is required in surgical emergency. Various scoring system have been designed successfully to assess the prognosis and outcome of peritonitis. The present study was carried out with an aim to evaluate the usefulness and severity of Mannheim peritonitis (MPI) score in comparison to acute physiological and chronic health evaluation II (APACHE II) scoring system for prediction of the outcome in patients with perforation peritonitis and thus decision making in perforation peritonitis. Methods: A prospective observational study was carried out at Department of Surgery, King George’s Medical University (KGMU), Lucknow for a period of one year from July 2018 to June 2019. A total of 100 patients were enrolled in the study. Results: Majority of patients were males compared to females. Maximum number of patients (40%) was aged 51-60 years. Maximum number of patients (42%) had duodenal perforation. A significant association between higher MPI scores and mortality was seen (p<0.001). Statistically, the association between APACHE II scores and mortality was significant (p<0.001). Conclusions: APACHE II had a slightly higher sensitivity as well as specificity as compared to MPI. MPI is easy to calculate but accuracy of APACHE II is more, compared to MPI.